Food labels. Consumer understanding of the information contained. A pilot study - Avram, Calin; Avram, Laura; Rus, Victoria; Georgescu, Ion Mihai; Ruta, Florina; Olah, Peter (Progress in Nutrition, 2022)
Introduction. Food labels are very important when choosing healthy foods. Another important element that is found on the food label are alimentary additives that are added to the food to increase the shelf life or taste. Aim. The aim of our study is to identify how respondents understand and are aware of the information found on food labels. It is very important to be able to choose products that meet the consumers’ needs and that do not affect their health. Methods. In order to carry out this pilot study, cross-sectional descriptive, an online evaluation questionnaire was developed and disseminated between December 2016 and February 2017. Results. Out of the total of 476 participants in the study, the persons with higher or higher education represent over 80% of the respondents. Women are the most representative in this study almost 80% as well as people in urban areas. We can identify the association between the age of the participants and their residence (p = 0.0038), the education of the participants (p <0.001), the people who decide upon the products purchased (p = 0.039), reading the labels before purchasing (p <0.001). Conclusions. According to our study, the perception of information on food labels is very low. Information on the elements that allow the correct choice for buyers, both about food additives and about nutritional values could be beneficial for the health of the buyer.